Lucchesiite, CaFe2+3Al6(Si6O18)(BO3)3(OH)3O, a new mineral species of the tourmaline supergroup. (1st February 2017) - Bosi, Ferdinando; Skogby, Henrik; Ciriotti, Marco; Gadas, Petr; Novák, Milan; Cempírek, Jan; Všianský, Dalibor; Filip, Jan
Lucchesiite, CaFe2+3Al6(Si6O18)(BO3)3(OH)3O, is a new mineral of the tourmaline supergroup. It occurs in the Ratnapura District, Sri Lanka (6°35'N, 80°35'E), most probably from pegmatites and in Mirošov near Strážek, western Moravia, Czech Republic, (49°27'49.38"N, 16°9'54.34"E) in anatectic pegmatite contaminated by host calc-silicate rock. Crystals are black with a vitreous lustre, conchoidal fracture and grey streak. Lucchesiite has a Mohs hardness of ∼7 and a calculated density of 3.209 g/cm3 (Sri Lanka) to 3.243 g/cm3 (Czech Republic). In plane-polarized light, lucchesiite is pleochroic (O = very dark brown and E = light brown) and uniaxial (–). Lucchesiite is rhombohedral, space group R3m, a ≈ 16.00 Å, c ≈ 7.21 Å, V ≈ 1599.9 Å3, Z = 3. The crystal structure of lucchesiite was refined to R1 ≈ 1.5% using ∼2000 unique reflections collected with MoKα X-ray intensity data. Crystal-chemical analysis for the Sri Lanka (holotype) and Czech Republic (cotype) samples resulted in the empirical formulae, respectively: X(Ca0.69Na0.30K0.02)∑1.01Y(Fe2+1.44Mg0.72Al0.48Ti4+0.33V3+0.02Mn0.01Zn0.01)∑3.00Z(Al4.74Mg1.01Fe3+0.25)∑6.00[T(Si5.85Al0.15)∑6.00O18](BO3)3V(OH)3W[O0.69F0.24(OH)0.07]∑1.00 and X(Ca0.49Na0.450.05 K0.01)∑1.00Y(Fe2+1.14Fe3+0.95Mg0.42Al0.37Mn0.03Ti4+0.08Zn0.01)∑3.00Z(Al5.11Fe3+0.38Mg0.52)∑6.00[T(Si5.88Al0.12)∑6.00O18](BO3)3V[(OH)2.66O0.34]∑3.00W(O0.94F0.06)∑1.00. Lucchesiite is an oxy-species belonging to the calcic group of the tourmaline supergroup. The closest end-member composition of a valid tourmaline species is that of feruvite, to which lucchesiite is ideally related by the heterovalent coupled substitution ZAl3++O1O2– ↔ ZMg2+ + O1(OH)1–. The new mineral was approved by the International Mineralogical Association Commission on New Minerals, Nomenclature and Classification (IMA 2015-043).